2019
DOI: 10.1302/1863-2548.13.190043
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of paediatric elbow fractures: A retrospective multi-centre study of 488 fractures

Abstract: PurposeElbow fractures are common in children and occur during daily activities. The aim of this study is to evaluate the epidemiology of paediatric elbow fractures over a two-year period in Okinawa, a southern subtropical island in Japan.MethodsThis was a retrospective study of 488 elbow fractures in children younger than 15 years old treated at 11 hospitals in Okinawa. Data included age, gender, calendar month, type of fracture, operation rate, mechanism of injury, and aetiology.ResultsThe most frequent age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
40
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 16 publications
5
40
1
Order By: Relevance
“…Conservative treatments were chosen primarily in nondisplaced and isolated elbow fracture which stabilized by immobilization. This is in contrast with the previous epidemiology study from Houshian et al which applied a much more conservative method for the treatment of the elbow fracture in children [14], but in line with the study investigated by Okubo et al [2] in the term of higher operative rate for Gartland type II and type III supracondylar fractures (50% and 100% operative rate). In this study, the most common injury is Gartland type III, thus the operative method rate is higher.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…Conservative treatments were chosen primarily in nondisplaced and isolated elbow fracture which stabilized by immobilization. This is in contrast with the previous epidemiology study from Houshian et al which applied a much more conservative method for the treatment of the elbow fracture in children [14], but in line with the study investigated by Okubo et al [2] in the term of higher operative rate for Gartland type II and type III supracondylar fractures (50% and 100% operative rate). In this study, the most common injury is Gartland type III, thus the operative method rate is higher.…”
Section: Discussionsupporting
confidence: 68%
“…Similar result about the occurrence of supracondylar fractures is reported by Okubo et al in the study about pediatric elbow fractures. It is reported that the number of supracondylar fractures is the most compared to other elbow fracture in pediatric population with 214 cases from the total of 488 patient populations [2].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In displaced LCFH and MCFH, open reduction and internal fixation (ORIF) is our preferred choice and usually yields satisfactory outcomes [27,28]. Whereas, closed reduction and percutaneous pinning (CRPP) remains the primary choice for displaced SCFH [29]. Regardless of the fracture type and operative choice, the pain response was significantly lower in the GA + BPB group in our study.…”
Section: Discussionmentioning
confidence: 61%